Efficacy of bio-pesticide Lecanicillium lecanii against soybean-sucking bugs Riptortus linearis during field application - YAYUK MULYATI; SITI ZUBAIDAH; YUSMANI PRAYOGO (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Mulyati Y, Zubaidah S, Prayogo Y. 2023. Efficacy of bio-pesticide Lecanicillium lecanii against soybean-sucking bugs Riptortus linearis during field application. Biodiversitas 24: 4829-4836. This study aimed to determine the effect of application time and surfactants on the efficacy of Lecanicillium lecanii strain Probolinggo in controlling the soybean pod-sucking bug Riptortus linearis in a field test. The study was conducted in a randomized block design consisting of two treatments, namely time of application (7 am, 10 am, 1 pm, and 4 pm) and type of surfactant (alkyl glycerol phthalate and alkylaryl polyglycol ether). Application time at 4 pm showed 93% highest mortality of R. linearis than the other treatments, with the lowest number of punctures (86 punctures) and the highest soybean dry weight (11.38 g), which were not significantly different from the application time of 10 am. The efficacy of L. lecanii increased by 74.3% after adding alkylaryl polyglycol ether. The efficacy of L. lecanii with alkyl glycerol phthalate was not significantly different from the control. In the parameters of the number of seed punctures and dry weight of soybeans, the surfactant treatment gave similar results to the control. The results showed that in the field test, the highest efficacy of L. lecanii against R. linearis occurred at 4 pm with alkil aril polyglycol ether surfactant.